Modeling the Function of TATA Box Binding Protein in Transcriptional Changes Induced by HIV-1 Tat in Innate Immune Cells and the Effect of Methamphetamine Exposure - Tjitro, Ryan; Campbell, Lee A.; Basova, Liana; Johnson, Jessica; Najera, Julia A.; Lindsey, Alexander; Marcondes, Maria Cecilia Garibaldi (Frontiers in Immunology, 2019)
Innate immune cells are targets of HIV-1 infection in the Central Nervous System (CNS), generating neurological deficits. Infected individuals with substance use disorders as co-morbidities, are more likely to have aggravated neurological disorders, higher CNS viral load and inflammation. Methamphetamine (Meth) is an addictive stimulant drug, commonly among HIV+ individuals. The molecular basis of HIV direct effects and its interactions with Meth in host response, at the gene promoter level, are not well understood. The main HIV-1 peptide acting on transcription is the transactivator of transcription (Tat), which promotes replication by recruiting a Tata-box binding protein (TBP) to the virus long-terminal repeat (LTR). We tested the hypothesis that Tat can stimulate host gene expression through its ability to increase TBP, and thus promoting its binding to promoters that bear Tata-box binding motifs. Genes with Tata-box domains are mainly inducible, early response, and involved in inflammation, regulation and metabolism, relevant in HIV pathogenesis. We also tested whether Tat and Meth interact to trigger the expression of Tata-box bearing genes. The THP1 macrophage cell line is a well characterized innate immune cell system for studying signal transduction in inflammation. These cells are responsive to Tat, as well as to Meth, by recruiting RNA Polymerase (RNA Pol) to inflammatory gene promoters, within 15 min of stimulation (1). THP-1 cells, including their genetically engineered derivatives, represent valuable tools for investigating monocyte structure and function in both health and disease, as a consistent system (2). When differentiated, they mimic several aspects of the response of macrophages, and innate immune cells that are the main HIV-1 targets within the Central Nervous System (CNS). THP1 cells have been used to characterize the impact of Meth and resulting neurotransmitters on HIV entry (1), mimicking the CNS micro-environment. Integrative consensus sequence analysis in genes with enriched RNA Pol, revealed that TBP was a major transcription factor in Tat stimulation, while the co-incubation with Meth shifted usage to a distinct and diversified pattern. For validating these findings, we engineered a THP1 clone to be deficient in the expression of all major TBP splice variants, and tested its response to Tat stimulation, in the presence or absence of Meth. Transcriptional patterns in TBP-sufficient and deficient clones confirmed TBP as a dominant transcription factor in Tat stimulation, capable of inducing genes with no constitutive expression. However, in the presence of Meth, TBP was no longer necessary to activate the same genes, suggesting promoter plasticity. These findings demonstrate TBP as mechanism of host-response activation by HIV-1 Tat, and suggest that promoter plasticity is a challenge imposed by co-morbid factors such as stimulant drug addiction. This may be one mechanism responsible for limited efficacy of therapeutic approaches in HIV+ Meth abusers.